Phoneme recognition in bimodal hearing. (1st October 2020) - Shpak, Talma; Most, Tova; Luntz, Michal
Abstract: Background: Many unilateral cochlear implant (CI) users have residual hearing in the nonimplanted ear, allowing them to use bimodal hearing. Assessing the hearing aid (HA) contribution is important. Objective: To examine the contribution of a contralateral HA in unilateral CI users with severe-profound hearing loss (HL) in the non-implanted ear to phonetic features perception. Participants and method: Monosyllabic word test in noise was used to assess the phonetic features perception in 29 adult bimodal users with severe-profound HL and only minimal speech recognition using HA alone in the nonimplanted ear. Results: For all consonants and vowel features, participants scored better in the bimodal condition than in the CI-alone condition. Better low frequencies thresholds in the HA ear correlated with better perception of phonetic features in the bimodal condition. Conclusion: CI/HA users with only minimal speech recognition using HA alone in the nonimplanted ear extract low-frequency information provided by the HA ear and combine it with information coming from the implanted ear. Significance: The results of the study provide a reasoning for unilateral CI users to insist on using a contralateral HA as long as contralateral implantation is not performed, and suggest how to monitor the benefit derived from the HA.